(3CSFdI efdG LdHjs - (3GdBeOj GdcQOj, edG LdHj, eMeO Hf Ydj (B, 1066 (3g`s
(3ChdgG (B:s
(3fMeOc Gddg MeO GdeJhGVYjf Ydi HGHc agPg eSGFd eJYOOI heHGMK eJLOOI LeYfG eHOJC ef GdEfGA Edi GdCYdi hef CSgd Edi GdCUYH GdCbUi hLYdJgG HYOeG LeYJgG gOjI Edis
(3BNQgG (B:s
(3GdeSCdI GdJGSYI aj GdgfOSI eG bGdg GdeMbb aj LhGH Pdc Gdbhd Gfg djS dTjA dCf Pdc GdJbOjQ GfeG jKJVj YOe GfJgGA GdhSGFW GdeecfI dGSJMGdI JbdjdgG aEfg Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\499s
(3cTa GdXfhf (B1\81s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdeYGQa GdYGeIs